Systematic screening of Drosophila deficiency mutatations for embryonic phenotypes and orphan receptor ligands. - Wright, A.P.; Fox, A.N.; Johnson, K.G.; Zinn, K. (PLoS ONE, 2010)
This paper defines a collection of Drosophila deletion mutations (deficiencies) that can be systematically screened for embryonic phenotypes, orphan receptor ligands, and genes affecting protein localization. It reports the results of deficiency screens we have conducted that have revealed new axon guidance phenotypes in the central nervous system and neuromuscular system and permitted a quantitative assessment of the number of potential genes involved in regulating guidance of specific motor axon branches. Deficiency "kits" that cover the genome with a minimum number of lines have been established to facilitate gene mapping. These kits cannot be systematically analyzed for phenotypes, however, since embryos homozygous for many deficiencies in these kits fail to develop due to the loss of key gene products encoded within the deficiency. To create new kits that can be screened for phenotype, we have examined the development of the nervous system in embryos homozygous for more than 700 distinct deficiency mutations. A kit of approximately 400 deficiency lines for which homozygotes have a recognizable nervous system and intact body walls encompasses >80% of the genome. Here we show examples of screens of this kit for orphan receptor ligands and neuronal antigen expression. It can also be used to find genes involved in expression, patterning, and subcellular localization of any protein that can be visualized by antibody staining. A subset kit of 233 deficiency lines, for which homozygotes develop relatively normally to late stage 16, covers approximately 50% of the genome. We have screened it for axon guidance phenotypes, and we present examples of new phenotypes we have identified. The subset kit can be used to screen for phenotypes affecting all embryonic organs. In the future, these deficiency kits will allow Drosophila researchers to rapidly and efficiently execute genome-wide anatomical screens that require examination of individual embryos at high magnification.